The Nordic Model and Structural Change: Lessons from the Collapse of Saab Automobile AB - Mark T. Nance; Jack Daly (Intereconomics, 2018)
The case of Saab and Trollhättan shows one way that societies can harness the productive side of creative destruction while mitigating the harm it causes.
Keywords: 330